JUDICIAL PROTECTION OF UKRAINE’S CULTURAL HERITAGE IN THE CONTEXT OF ECONOMIC CHALLENGES - Andrii Falkovskyi; Vasyl Slipeniuk; Lidiya Chorna (Baltic Journal of Economic Studies)
Ukraine's cultural heritage is a fundamental component of its sustainable economic development, necessitating systematic financial support. In the context of prevailing economic challenges, state financial assistance for cultural heritage sites is undergoing a decline. Concurrently, the significance of these sites is heightened during periods of war, serving as markers of national identity. The present article is dedicated to the exposition of the particularities of judicial protection of cultural heritage in the context of economic challenges. The authors of this study have sought to define the essence of cultural heritage and the substantive content of its constituent elements, which are both tangible and intangible. It is important to note that cultural heritage serves as a foundation for the country's economic development in the cultural and tourism spheres. Furthermore, it has been observed that cultural heritage unites the Ukrainian political nation around the idea of civic identity in the face of existential threats. The researchers identified the economic determinants of cultural heritage preservation in Ukraine, including international financial support, national funding sources, and state guarantees for financing heritage protection. The following proposal is put forward for consideration: that a legal framework be established for the purpose of the judicial protection of cultural heritage in Ukraine, including its fundamental elements. The article dedicates a significant portion of its discourse to the intricacies of implementing judicial protection mechanisms for cultural heritage in Ukraine. It has been posited that judicial authorities are capable of protecting cultural heritage objects through two principal approaches: the establishment of legal accountability for individuals (criminal, administrative, or civil liability), and the resolution of legal disputes within commercial and administrative proceedings, conditional upon the protection of these objects. The study's findings underscore the imperative for comprehensive judicial consideration and the establishment of a robust internal conviction among judges concerning the significance of safeguarding cultural heritage for posterity.